Acid-labile subunit (ALS) deficiency - Domene, Horacio Mario (2011)
The acid-labile subunit (ALS) protein is crucial for maintaining the integrity of the circulating IGF/IGFBP system. In humans, complete ALS deficiency is characterized by severely reduced serum IGF-I and IGFBP-3 concentrations that is incongruent with the associated mild growth retardation (height SDS -2 to -3 SDS before and during puberty). Twenty-one patients have been described with ALS deficiency, representing 16 unique homozygous or compound heterozygous inactivating mutations of the IGFALS gene. Pubertal delay in boys and insulin insensitivity are common findings. In the assessment of a child with short stature ALS deficiency should be consider in those patients presenting: 1) a normal response to GH stimulation test, 2) low IGF-I levels associated with more profoundly reduced IGFBP-3 levels, 3) a mild growth retardation, apparently out of proportion to the degree of IGF-I and IGFBP-3 deficits, 4) lack of response to an IGF generation test and 5) insulin insensitivity.